THE MOBILIZATION FUNCTION OF THE NEWSPAPER POLITIKA AT THE BEGINNING OF THE FIRST BALKAN WAR - Aleksić, Dušan (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
At the beginning of the 20th century, political print media in Serbia was on the rise due to the liberal Constitution from 1901 and the media law from 1904. The daily Politika was among the newly founded newspapers and it soon became the most popular one because of the selection of topics, the manner of reporting and simplified language and style. Using content analysis, in this article we examine if and how Politika managed to accomplish the mobilization function in reporting at the beginning of the First Balkan War in 1912, having in mind its popularity and influence, as well as the fact it was the first war conflict since the establishment of the paper. The main focus of the research is on propaganda techniques, and linguistic and stylistic tools which Politika used to influence its readers. The analysis showed that, even though it was young media publication at the time, Politika was ready for the beginning of the war and it successfully accomplished its mobilization function, which indicates the importance and power of the media in war circumstances.